A survey of undergraduate medical students’ knowledge and attitudes about gender bias: the Newfoundland and Labrador perspective - Maxwell, Erika; Sheppard, Gillian; Yi, Yanqing (Canadian Medical Education Journal, 2024)
Background: Female physicians and patients experience gender bias in healthcare. The purpose of this research is to explore medical students’ gender bias toward physicians and patients and whether their bias varies by gender. Methods: We surveyed medical students at Memorial University between November 2020 and April 2021. We recruited participants through Facebook, email, and e-posters. We collected demographic information, including gender and class year. We used the Nijmegen Gender Awareness in Medicine Scale to measure gender sensitivity, gender role ideology toward patients, and gender role ideology toward doctors. We analyzed the data using averages and t-tests. Results: Mean gender sensitivity scores were 4/5 indicating high gender sensitivity. Gender role ideology toward doctors mean scores were 2/5 indicating that students did not hold strong stereotypical views toward doctors. Although male students scored higher than female students (p<.05), mean scores for gender role ideology toward patients were low for both male and female students (x̄<2), indicating low stereotyping toward patients. Conclusions: We found that students held largely non-biased ideologies surrounding gender in medicine and that female students were even less biased than male students for gender role ideology toward patients.